Dress as a mark of differentiation: the religious symbolism of dress in African initiated churches - Vengeyi, Elizabeth; Mwandayi, Canisius (University of Bamberg Press, 2016)
Dress as a Mark of Differentiation The Religious Symbolism of Dress in African Initiated Churches